PRODUKTIVITAS SERASAH DI LAHAN REHABILITASI MANGROVE KELURAHAN SETAPUK BESAR KOTA SINGKAWANG - Herlina Darwati; Destiana Destiana (Universitas Tanjungpura, 2022)
This study aims to determine the amount of litter production of the amount of carbon (C-org), nitrogen (N), and phosphorus (P) nutrients in the substrate of rehabilitated mangrove forests in Setapuk Besar Village, Singkawang City. Determination of observation points using the purposive sampling method based on mangrove planting years in 2007, 2010, 2013, and 2016. Mangrove leaf litter collection uses a litter trap measuring 1 m x 1m with a periodic retrieval time of every 2 weeks. Data collection of environmental factors is carried out directly in the field at each observation point. Measurements of substrate nutrient content with parameters C-org, N and P were carried out on substrate samples at each observation point for later analysis in the laboratory. The results showed that the productivity of litter in the mangrove rehabilitation area of Setapuk Besar Village, Singkawang City was 7.41 gbk / m2 / day – 0.917 gbk / m2 / day. The largest productivity came from mangroves in 2007 which contributed 56% of the total annual litter production with the largest component coming from the leaf part of the mangrove plant. The highest amount of carbon (C-org), N and P nutrient content was in the 2007 growing year. which shows the successful rehabilitation of mangrove lands increases the fertility of mangrove substrates.Keywords: Litter production, Mangrove, Rehabilitation, Setapuk AbstrakPenelitian ini bertujuan untuk mengetahui jumlah produksi serasah jumlah kandungan unsur hara karbon (C-org), nitrogen (N) dan fosfor (P) pada substrat hutan mangrove rehabilitasi di Kelurahan Setapuk Besar Kota Singkawang. Penentuan titik pengamatan menggunakan metode purposive sampling berdasarkan tahun tanam mangrove tahun 2007, 2010, 2013 dan 2016. Pengumpulan serasah daun mangrove menggunakan litter trap berukuran 1 m x 1m dengan waktu pengambilan berkala disetiap 2 minggu. Pengumpulan data faktor lingkungan dilakukan secara langsung dilapangan pada setiap titik pengamatan. Pengukuran kandungan hara substrat dengan parameter C-org, N dan P dilakukan terhadap sampel substrat di setiap titik pengamatan untuk kemudian dianalisis di laboratorium. Hasil penelitian menunjukkan produktifitas serasah di lahan rehabilitasi mangrove Kelurahan Setapuk Besar Kota Singkawang sebesar 7,41 gbk/m2/hari – 0,917 gbk/m2/hari. Produktivitas terbesar berasal dari mangrove tahun tanam 2007 yang menyumbangkan 56% dari total produksi serasah tahunan dengan komponen terbesar yang berasal dari bagian daun tanaman mangrove. Jumlah kandungan unsur hara karbon (C-org), N dan P tertinggi berada pada tahun tanam 2007. yang menunjukkan berhasilnya rehabilitasi lahan mangrove ini meningkatkan kesuburan substrat mangrove. Kata Kunci : Mangrove, Produktivitas serasah , Rehabilitasi Setapuk.